2010
DOI: 10.1139/b10-041
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival patterns of Cardiocrinum cordatum var. glehnii (Liliaceae) based on a 13-year monitoring study: Life history characteristics of a monocarpic perennial herb

Abstract: Based on 13 years of monitoring, the fates of individuals and contributions of size and age to demography through the life-history from seedling to flower were investigated in a monocarpic perennial herb, Cardiocrinum cordatum (Thunb.) Makino var. glehnii (F. Schmidt) H. Hara. Of 6155 seedlings, 5264 (85.5%) and 852 (13.8%) plants died at the seedling and one-leaf stage during the 13 years, respectively. Twelve individuals (0.40%) at the three- to seven-leaf stage reproduced after vegetative growth for 7–11 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The former is scattered in isolated patches across the Himalaya—Hengduan Mountains (including Bhutan, northeast India, Myanmar, Nepal, Sikkim), Southwest, and Central China (Phartyal et al, 2012), whereas C. cathayanum mainly occurs in isolated stands of montane deciduous forests in Southeast China. By contrast, C. cordatum is native to Japan and certain islands in the Russian Far East (Sakhalin, Kuriles; Araki et al, 2010). All three species of Cardiocrinum have self-compatible, visually showy flowers, and are insect (many bumblebee species) pollinated flowers that mature into capsules containing several 100 seeds with thin filmy wings (Ohara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The former is scattered in isolated patches across the Himalaya—Hengduan Mountains (including Bhutan, northeast India, Myanmar, Nepal, Sikkim), Southwest, and Central China (Phartyal et al, 2012), whereas C. cathayanum mainly occurs in isolated stands of montane deciduous forests in Southeast China. By contrast, C. cordatum is native to Japan and certain islands in the Russian Far East (Sakhalin, Kuriles; Araki et al, 2010). All three species of Cardiocrinum have self-compatible, visually showy flowers, and are insect (many bumblebee species) pollinated flowers that mature into capsules containing several 100 seeds with thin filmy wings (Ohara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, information about the population structure of monocarpic perennials is rare (Araki et al . ). It was reported that the age structure of Heracleum mantegazzianum (Apiaceae) varied according to the habitat (Pergl et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, the mortality of seedlings and small one‐leaf sterile individuals appeared to be very high (Araki et al . ), and very few plants reached maturity from seed. On the other hand, mature plants normally produced one or two vegetative offshoots per plant (Ohara et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival rate of seedlings is extremely low, and it takes many years for juveniles to reach the flowering stage. Thus, individuals recruited by bulblet formation can bypass crucial small juvenile stages with high mortality and therefore there is a higher probability that they may survive (Ohara et al ; Araki et al ).…”
Section: Methodsmentioning
confidence: 99%